Infection by intestinal parasites in disabled patients and their guardians - Martins, Eluane de Luca S; Pereira, Adriano; Castilho, Vera Lucia Pagliusi; Gonçalves, Elenice Messias do Nascimento; Lallo, Maria Anete (Revista de Ciências Médicas e Biológicas, 2022)
Introduction: intestinal parasitic infections are common major problem closely related to poverty, inadequate sanitation, insufficient health care and overcrowding. They cause significant morbidity among institutionalized patients, however, there are few studies that analyze the frequency of intestinal parasites in disabled patients that are not institutionalized. Objective: the aim of the present study was to determine the prevalence of intestinal parasitic infection in disabled patients and their guardians. Methodology: a total of 336 fecal samples were collected from 53 disabled patients and history of diarrhea during the study period and 31 guardians, parents and professional staff of Institution. Parasite research was carried out using zinc sulphate centrifugal-flotation technique, Lutz/Hoffman Pons and Janer method, Rugai method and Gram-Chromotrope, Leishman, Kinyoun, Kato-Katz and Trichrome stains were used. Results: we found 15.5% of positive sample for enteroparasites in all analyzed individuals (13/84), with 11.3% (6/53) of prevalence in disabled patients and 22.5% (7/31) for guardians, with significant difference. There was no difference between gender, but there was a higher number of positives in patients between 6 and 11 years of age. Monoparasitism and the presence of protozoa, especially Blastocystis hominis, were the most prevalent conditions. Conclusions: despite the aforementioned intrinsic susceptibility of patients with special needs, the prevalence of intestinal parasites was low. In guardians, the prevalence was higher, suggesting extreme attention to the care process, which may have prevented the transmission to their disabled patients contact.